2018
DOI: 10.3329/uhj.v12i2.36389
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Angiographic Findings Among the Left Bundle Branch Block Patients

Abstract: Introduction: Complete Left bundle branch block(LBBB) increases the risk of cardiac mortality, and prognosis is primarily determined by the underlying coronary artery diseases. The goal of this study was to determine the association of complete left bundle branch block (LBBB), with site, severity & risk factors of coronary artery disease (CAD) diagnosed by coronary angiogram(CAG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…A study evaluating the angiographic characteristics of symptomatic patients with major LBBB concluded that this is rather correlated with normal epicardial arteries; more precisely, 64% of patients had angiographic results without changes [ 21 , 22 , 23 ], which was also demonstrated in our research. However, this study, as well as most of the literature studies addressing this subject, does not describe the differences between the two sexes from the point of view of the grade or type of coronary involvement.…”
Section: Discussionsupporting
confidence: 80%
“…A study evaluating the angiographic characteristics of symptomatic patients with major LBBB concluded that this is rather correlated with normal epicardial arteries; more precisely, 64% of patients had angiographic results without changes [ 21 , 22 , 23 ], which was also demonstrated in our research. However, this study, as well as most of the literature studies addressing this subject, does not describe the differences between the two sexes from the point of view of the grade or type of coronary involvement.…”
Section: Discussionsupporting
confidence: 80%